Digital banking penetration in underserved communities in South Africa - Mdluli, Ntokozo (University of the Witwatersrand, Johannesburg, 2022)
This purpose of this research paper is to investigate the impact that the closing of bank branches and the influence of digital banking as an alternative has on the banking population in underserved communities. For the purposes of the study, these communities are those that face barriers and challenges in gaining access to and using resources. Access to electricity, problems with broadband infrastructure or internet connectivity, employment, language, and literacy are just a few of the issues. With the rapid rate of bank branch closures globally and in South Africa, which are due to a variety of factors such as operational cost savings for banking institutions, looting unrest that resulted in property destruction, and the rate of digitalization, underserved communities are at risk of becoming financially excluded. The study sought to answer four research questions. Understanding the factors that influence underserved communities' banking activities, investigating the impact of traditional banking channel closures such as bank branches on underserved communities, determining whether the traditional banking channel closures result in financial exclusion of underserved communities, and making recommendations to banking institutions on how to lessen the impact of traditional banking channel closures. As part of the study, the researcher used a quantitative research approach, distributing a questionnaire to 179 members of underserved communities across South Africa. The key findings of the research showed that the results for two out of four hypotheses were statistically significant. We were able to show that the closure of bank branches increases the use of digital banking in underserved communities and may result in financial exclusion of people in underserved communities. In contrast to the literature review findings, we discovered that bank branches have no influence or impact on the community in underserved areas, and that issues with electricity and internet connectivity, a lack of digital literacy, and security concerns do not prevent underserved communities from using digital banking
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2022
Keywords: Digital banking; Financial exclusion; Underserved communities; Digital divide; Digital finance; Banking institutions; Digital literacy; UCTD; SDG-11: Sustainable cities and communities